Strategies for Pedagogical Interventions to Develop Emotional Intelligence (EI) of Employees in a Hybrid Work Schedule - Matulčíková, Marta; Breveníková, Daniela; Vaľko, Michal; Gawrych, Roman; Procházka, David A. (Ital Publication, 2024)
The purpose of the research article is to identify the educational methods suitable for developing employee emotional intelligence. The focus was on the number of hours that small and medium sized enterprises are willing to invest in training their employees in emotional intelligence and on the benefits, i.e., changes in work outcomes as evaluated by respondents. The questionnaire method and interviews were used to obtain data from respondents, line managers, and education managers. Based on correlation coefficient calculations, brainstorming was identified as a frequently used method of active learning, which is related to the physical presence in the learning premises. The analysis of the responses of the respondents and their calculation using the correlation coefficient surprisingly showed that the lecture method gained great support and was considered by the respondents, i.e., managers and education managers, as very important to achieve the cognitive, affective, and psychomotor goals of education. Moreover, it was assessed as a method suitable for remote learning, i.e., for virtual educational spaces. Doi: 10.28991/ESJ-2024-08-05-023 Full Text: PDF